Pengembangan Media Lembar Balik Tentang Kesehatan Ibu Hamil dan Balita di kecamatan Sukasari Bandung - Hendiarti, Silma Syanindita; Widiaty, Isma; Rinekasari, Nenden Rani (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2020)
Posyandu has an important role in improving the quality of maternal and child health through the health service process, so the use of supporting tools such as flipcharts is very helpful when conducting counseling. Posyandu at the Sukasari District in Bandung, the use of flipchart media in the Posyandu counseling activity helped cadres to provide explanations because some cadres were still technologically illiterate. On the other hand, infographic media is also needed in counseling because infographic is a visualization of data to provide information represented through graphic objects, so it is interesting and easy to understand. Based on this analysis, the researcher developed infographic flipchart media on the health of pregnant women and toddlers in the Posyandu Sukasari District, Bandung by implementing expert judgment. This research uses the RD method, adopts research and development steps using the PPE model so the researcher only carries out three stages such as planning, production and evaluation. The results of the development of infographic flipchart media have been validated by media experts and Posyandu material experts. The results of the validation of the development of flipchart media about the health of pregnant women and toddlers in Posyandu Sukasari District, Bandung made by researcher are very feasible to be used for extension activities and as research material. Even so, the validator also provides comments or nests to perfect the flipchart media developed by researcher.